Cluster headache and macroprolactinoma: Case report of a rare, but potential important causality. (June 2017) - Andereggen, Lukas; Mono, Marie-Luise; Kellner-Weldon, Frauke; Christ, Emanuel
Highlights: Refractory cluster headache (CH) secondary to a macroprolactinoma is a rare entity. Medical treatment with dopamine agonists allowed for permanent recovery. Measurement of prolactin levels and MRI might be considered in these patients. Abstract: While headache is not an uncommon symptom in patients suffering from pituitary adenomas, cluster headache (CH) has rarely been reported in such cases. Headache associated with hyperprolactinemia has been reported to be responsive to dopamine agonists (DA agonists) in many patients. We report on a patient with refractory CH secondary to a macroprolactinoma who showed immediate and permanent clinical and radiologic recovery following medical treatment with DA agonists. Measurement of prolactin levels in addition to cranial magnetic resonance imaging might be considered in patients with refractory CH, until the significance of this potential causality becomes clearer.